PERTUMBUHAN EKONOMI, KETIMPANGAN WILAYAH DAN KEMISKINAN DI PROVINSI BANTEN - Sumiyarti Sumiyarti (Media Ekonomi, 2018)
This study aims to determine the development of economic and social indicators, namely the rate of economic growth, regional development inequality and poverty levels in Banten Province, with the period 2002-2016. This study used the cross-tabulation methods and correlation analysis in the provincial scope data. The results of the analysis conducted concluded that the economic growth rate of Banten Province had a tendency to increase from 4.11 percent in 2002 and 5.28 percent in 2016. While the development inequality between regions in Banten Province as measured by the Williamson Index tended to decline in the 2002 period -2016. The fluctuating index of development inequality tended to decline from 0.57 in 2002 to 0.21 and again increased to 5.36 in 2016. The poverty rate in Banten Province also experienced a significant decline, from 9.22 percent in 2002 to 5, 36 percent in 2016. Furthermore, the results of the correlation analysis conducted provide the conclusion that the relationship between the variables of economic growth rates and the level of regional inequality and poverty is negative, with a weak level of relationship. While the correlation between the level of inequality and the level of poverty is positive with a strong level of relationship. In general, it was concluded that the development of the poverty rate in Banten Province corresponded or correlated with equitable development.